Synthesis and antimycobacterial evaluation of 5-alkylamino-N-phenylpyrazine-2-carboxamides - Zitko, Jan; Servusová, Barbora; Janoutová, Alena; Paterová, Pavla; Mandíková, Jana; Garaj, Vladimír; Vejsová, Marcela; Marek, Jan; Doležal, Martin (Bioorganic & medicinal chemistry, 2015)
Substitution of chlorine in 5-chloro-N-phenylpyrazine-2-carboxamide (1) with simple n-alkylamines yielded a series of 5-alkylamino-N-phenylpyrazine-2-carboxamides (propylamino to octylamino derivatives), which possessed similar or increased activity against Mycobacterium tuberculosis H37Rv compared to parent 5-chloro derivative (1), with MIC ranging from 2.5 to 12.2 μM. 5-Butylamino to 5-heptylamino derivatives exerted similar activity also against Mycobacterium kansasii. Importantly, the substitution led also to significant decrease of in vitro cytotoxicity in HepG2 cell line. 5-Heptylamino-N-phenylpyrazine-2-carboxamide (1e) exerted MIC=2.5 μM (M.tbc) and IC50 >250 μM (HepG2). Further modification of alkylamino chain with terminal methoxy or hydroxy group lead to compounds with decreased or none activity, the decrease was proportional to the decrease of lipophilicity. 5-(2-Phenylethylamino) and 5-(3-phenylpropylamino) derivatives were also of decreased activity. On contrary to alkylamino derivatives derived from 1, alkylamino derivatives derived from 5-chloro-N-2-chlorophenylpyrazine-2-carboxamide (2) possessed substantially decreased or none activity. None of the prepared compounds was active against Mycobacterium avium.
Keywords: Pyrazinamide; Antitubercular Agents; Humans; vztahy mezi strukturou a aktivitou; Permeability; tuberkulóza; Cytotoxicity; lidé; Alkylamino derivatives; Amides; Antituberculars; antibakteriální látky; pyrazinamid; Anti-Bacterial Agents; Tuberculosis; Structure-Activity Relationship; amidy; antituberkulotika